Type 2 diabetes worsens the outcome of ischemia/reperfusion in female STEMI patients and female db/db mice with HFpEF cardiometabolic phenotype - Ivana Iveljic; Megan Young; Elvira Corhodzic; Fenn Cullen; Hiran A. Prag; Michael P. Murphy; Dunja Aksentijevic (Cardiovascular Diabetology)
Abstract Background Heart failure with preserved ejection fraction (HFpEF) poses a significant global health challenge, disproportionately affecting women. Diabetic women with HFpEF represent a high-risk subgroup, particularly after experiencing ST-segment elevation myocardial infarction (STEMI), exhibiting increased mortality compared to men. While prolonged door-to-balloon (DTB) times, reflecting delayed reperfusion, are a critical factor in STEMI outcomes, they alone do not fully capture the observed outcome variability in diabetic women. Using an integrated clinical and pre-clinical approach this study aimed to investigate the relative contributions of metabolic dysfunction and coronary artery disease (CAD) in type 2 diabetes (T2D) to STEMI outcomes in women, beyond the impact of DTB time. Methods A retrospective case–control study analysed female STEMI patients undergoing primary percutaneous coronary intervention (pPCI, n = 40 T2D, n = 40 non-diabetic controls), comparing clinical characteristics, treatment strategies, and early outcomes. A preclinical model (female db/db mice) assessed cardiac function via echocardiography, Langendorff perfusions, and ischemia–reperfusion protocols. Metabolome of heart, liver, and skeletal muscle was assessed by 1H NMR spectroscopy. Results Our study reveals significantly higher mortality, impaired left ventricular function post-pPCI, and increased implantable cardioverter-defibrillator (ICD) implantation rates in diabetic STEMI patients, irrespective of DTB time, when compared to non-diabetic controls. Elevated inflammatory markers, acute hyperglycaemia and evidence of cardio-hepatic damage were identified in T2D patients. db/db mice exhibited analogous T2D-associated pathophysiology, including increased ischemia–reperfusion injury exacerbated by metabolic disturbances in the myocardium, liver, and skeletal muscle versus non-diabetic controls. Conclusions In diabetic women, multiple factors beyond reperfusion delays exacerbate acute myocardial injury. This necessitates the development of sex-specific strategies to manage the cardiovascular complications of diabetic HFpEF. The db/db mouse model provides a relevant preclinical tool for future research as it mimics human T2D-associated HFpEF and STEMI outcome.